1980
DOI: 10.1007/bf01476867
|View full text |Cite
|
Sign up to set email alerts
|

Tissue culture in nephrology: Potential and limits for the study of renal disease

Abstract: Kidney cells, when isolated and cultivated in vitro, retain differentiated renal properties. Glomerular epithelial and mesangial cells from animal and human kidneys express their normal ultrastructure and the ability for basement membrane biosynthesis. Mesangial cells in culture have been utilized particularly for the study of hormonal tissue receptors, of prostaglandin production, and of their contractile response to various hormonal stimuli. Cells of tubule origin have been a valuable tool for the study of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…However, subsequent evidence suggests that the dominant cell in the dog kidney cell line, MDCK, has epithelial-cell properties. This conclusion was reached from the results of electrophysicochemical (Richardson et al, 1981), biochemical, hormonal (Ishizuka et al, 1978;Horster, 1980;Saier, 1981) and morphological (Rindler et al, 1979) studies. McRoberts et al (1981) concluded that 'MDCK cell monolayers are morphologically, functionally and biochemically similar to epithelia from the distal tubule of the kidney'.…”
Section: Discussionmentioning
confidence: 98%
“…However, subsequent evidence suggests that the dominant cell in the dog kidney cell line, MDCK, has epithelial-cell properties. This conclusion was reached from the results of electrophysicochemical (Richardson et al, 1981), biochemical, hormonal (Ishizuka et al, 1978;Horster, 1980;Saier, 1981) and morphological (Rindler et al, 1979) studies. McRoberts et al (1981) concluded that 'MDCK cell monolayers are morphologically, functionally and biochemically similar to epithelia from the distal tubule of the kidney'.…”
Section: Discussionmentioning
confidence: 98%
“…Several techniques are described for the culture of renal epithelia, some to be found in this journal issue and others in recent extensive review articles (1)(2)(3). Each individual technique has its particular virtues, and selection for use will depend on the nature of the questions being examined.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation and cultivation of a homogeneous and differentiated renal cell population in sufficient amounts for incuba tion experiments is difficult to accomplish. Recently, however, cultures of glomerular [1] and tubular cells [2,3] have been devel oped but most often have been used to mea sure either transport capabilities or hor monal responses. Only in relatively few cases have radiolabellcd precursor incuba tions been performed to study the synthesis of glycoproteins of whole glomeruli [4] and the glycosaminoglycan biosynthesis of epi thelial and mesangial cells [5].…”
Section: Introductionmentioning
confidence: 99%